Love thy neighbor: Religion and prosocial behavior - Guido Heineck (Bamberg University, Bamberg Economic Research Group (BERG), 2014)
There is a long tradition in psychology, the social sciences and, more recently though, economics to hypothesize that religion enhances prosocial behavior. Evidence from both survey and experimental data however yield mixed results and there is barely any evidence for Germany. This study adds to this literature by exploring data from the German Socio-Economic Panel (SOEP), which provides both attitudinal (importance of helping others, of being socially active) and behavioral components of prosociality (volunteering, charitable giving and blood donations). Results from analyses that avoid issues of reverse causality suggest mainly for moderate, positive effects of individuals' religious involvement as measured by church affiliation and church attendance. Despite the historic divide in religion, results in West and East Germany do not differ substantially.
Keywords: D64; Z12; Z13; 330; Religion; prosocial behavior; Germany